Figuring Firmaments Toward a Literary Structure: Toward a Literary Structure of the Hasidic Homily. - Moseson, Elly (Shofar: An Interdisciplinary Journal of Jewish Studies, 2025)
This essay clarifies the nature, function, and rhetorical power of the Hasidic homily by delineating three principal literary elements: the informative, a normative message pertaining to belief or practice; the interpretive, the hermeneutical techniques and strategies employed to interpret canonical texts; and the figurative, the images, metaphors, tropes, and narratives that appear in the discourse. To demonstrate the heuristic value of distinguishing these elements, this study analyzes two representative homilies, one by Dov Ber, the Maggid of Mezritsh [Międzyrzecz], and the other by Simhah Bunim of Peshischa [Przysucha]. Each text is presented in Hebrew alongside an English translation and the three components are visually parsed in both versions; this is followed by a detailed explication of the homily and an analytical discussion of the role each component plays within the whole. The conclusion contends that systematic attention to the informative, interpretive, and figurative elements not only facilitates the interpretation and comprehension of individual homilies, but can also help clarify what is distinctive about Hasidic literature and the continuities and differences among its various schools and subtraditions.